Intensity of statin therapy and muscle symptoms: a network meta-analysis of 153 000 patients - Susan C Weller; John W Davis (BMJ Open)
Objective To estimate relative risk (RR) of statin-associated musculoskeletal symptoms by statin therapy intensity.Setting Network meta-analysis assessing multicentre randomised controlled trials (RCTs) across several countries.Participants PubMed, Web of Science, Cochrane database and ClinicalTrials.gov were searched through January 2021 for doubled-blinded RCTs testing the effect of statin therapy on lipids with at least 1000 participants and 2 years of intended treatment. Two coders assessed articles for final inclusion, quality and outcomes. Treatment intensity was categorised according to American Heart Association definitions.Outcomes Pairwise and network meta-analysis (NMA) estimated RR and risk difference with random effects modelling. Heterogeneity was evaluated with the I2 statistic. Outcomes included muscle symptoms (any, myalgia and attrition due to muscle symptoms), rhabdomyolysis and elevated creatine kinase (CK) (>10 × upper limit of normal).Results Of 2919 RCTs, 24 (n=152 461) met inclusion criteria. NMA results indicated risk was significantly greater for high compared with moderate intensity statin therapy for any muscle problem (RR=1.04, 95% CI 1.00 to 1.07; I2=0%), myalgia (RR=1.04, 95% CI 1.00 to 1.08; I2=0%, number needed to harm (NNH)=173), attrition due to muscle problems (RR=1.37, 95% CI 1.09 to 1.73, I2=0%, NNH=218) and elevated CK (RR=4.69, 95% CI 2.50 to 8.80; I2=7%, NNH=527). Risk also was significantly higher for high intensity compared with placebo for any muscle problem (RR=1.05, 95% CI 1.01 to 1.09, I2=0%), myalgia (RR=1.13, 95% CI 1.05 to 1.23; I2=0%, NNH=182), attrition due to muscle problems (RR=1.55, 95% CI 1.15 to 2.08, I2=0%, NNH=187) and elevated CK (RR=5.37, 95% CI 2.48 to 11.61; I2=7%, NNH=589). Due to inconsistency of results across sensitivity analyses, estimates were inconclusive for rhabdomyolysis and CK. There were no significant differences in risk between moderate intensity therapy and placebo for all outcomes.Conclusions For approximately each 200 patients on high intensity statins, one additional patient may experience myalgia or discontinue therapy due to muscle problems compared with moderate intensity therapy.Trial registration number CRD42019112758.